2010
DOI: 10.3208/sandf.50.817
|View full text |Cite
|
Sign up to set email alerts
|

Technical Transition of Earth Structures for Shinkansen

Abstract: The paper describes the technical transition of earth structures for the super express known as the Shinkansen. To ensure the safe running of Shinkansen, the earth structures needed to be adequately designed and constructed with consideration of cost eŠectiveness and high stability. These earth structures include embankments for the slab tracks, reinforced retaining walls, reinforced cut slopes, aseismic abutments, soil improvement and performance-based design. New construction techniques and design methods, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Previous studies have reported that railway track degrades at a quicker rate in transitions zones between sections of the track with different characteristics and support conditions. 14 Transition zones between earthworks, bridges, viaducts or tunnels are some examples of these critical locations. To maintain adequate safety and quality levels, railway infrastructure managers need to perform frequent maintenance work, which is costly and reduces track availability.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that railway track degrades at a quicker rate in transitions zones between sections of the track with different characteristics and support conditions. 14 Transition zones between earthworks, bridges, viaducts or tunnels are some examples of these critical locations. To maintain adequate safety and quality levels, railway infrastructure managers need to perform frequent maintenance work, which is costly and reduces track availability.…”
Section: Introductionmentioning
confidence: 99%